Developments of real time and low cost VHF/UHF data acquisition system / Erwin Zulkarnain Idris - Idris, Erwin Zulkarnain (2017)
Very High Frequency (VHF)/Ultra High Frequency (UHF) plays a significant and vital role in our daily communications life. Thus, making it crucial to develop a data acquisition system to assist and facilitate further research and studies on VHF/UHF such as in amplitudes variations due to propagations characteristics, spectrum management and radio frequency information gathering in military/intelligence applications. Currently, available data acquisition systems (such as Spectrum Analyzer) are very expensive, complex (non-user friendly), rigid and limited capabilities due to its hardware restrictions/limitations. Consequently, a real-time and low-cost data acquisition system was developed by using microcomputer (Raspberry Pi 3b) and Software Defined Radio (RTL-SDR). The system successfully acquired and collected relevant data (e.g. frequency amplitudes) that would be resourceful for further analysis and studies of the VHF/UHF signals.